2020
DOI: 10.1021/acs.est.0c00245
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Secondary Plastic Particles Exhibit Limited Acute Toxicity but Chronic Effects on Daphnia magna

Abstract: Nanoplastics (NPs; <0.1 μm) are speculated to be a bigger ecological threat due to their predicted wider distribution, higher concentrations, and bioavailability. Primary NPs are manufactured to be that size, while secondary NPs originate from fragmentation of bigger debris. To date, the long-term impact of NPs in freshwater systems, particularly secondary NPs, is not well-understood. Thus, we employed a freshwater invertebrate, Daphnia magna, to investigate the chronic effects of model primary NPs, fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 51 publications
3
64
0
Order By: Relevance
“…Although plastics have significantly contributed to improvements in healthcare industry, building construction, electronics and contemporary human life in general, burgeoning build-up of improperly managed plastic wastes has raised concerns over their long-term health and ecotoxicological risks (Fahrenkamp-Uppenbrink, 2018;Ha and Yeo, 2018;Lei et al, 2018;Yu et al, 2018;Barletta et al, 2019;Besseling et al, 2019;Savoca et al, 2019;Adika et al, 2020;Bakir et al, 2020;Ding et al, 2020;Everaert et al, 2020;Fred-Ahmadu et al, 2020a;Fred-Ahmadu et al, 2020b;Lu et al, 2020;Na et al, 2020;Wilcox et al, 2020;Wong et al, 2020;Yu and Chan, 2020). Microplastics (MPs; 0.1 µm-5 mm) and nanoplastics (NPs; <0.1 µm) are ubiquitous and can accumulate in marine and freshwater ecosystems and exposed organisms, carrying chemical contaminants that are capable of posing considerable threats to human health, environment and aquatic life (de Souza Machado et al, 2018;Hartmann et al, 2019;Cole et al, 2020;Xu et al, 2020). Micro (nano) plastics (MNPs) are generally speculated to have increased environmental and health threats to marine organisms primarily due to their small size, predicted ubiquitousness, direct and indirect intake of plastic particles, bioavailability and enhanced concentrations of sorbed toxic chemicals (Setälä et al, 2018;Yu et al, 2018;Cole et al, 2020;Fred-Ahmadu et al, 2020a;Fred-Ahmadu et al, 2020b;Xu et al, 2020;Yu and Chan, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although plastics have significantly contributed to improvements in healthcare industry, building construction, electronics and contemporary human life in general, burgeoning build-up of improperly managed plastic wastes has raised concerns over their long-term health and ecotoxicological risks (Fahrenkamp-Uppenbrink, 2018;Ha and Yeo, 2018;Lei et al, 2018;Yu et al, 2018;Barletta et al, 2019;Besseling et al, 2019;Savoca et al, 2019;Adika et al, 2020;Bakir et al, 2020;Ding et al, 2020;Everaert et al, 2020;Fred-Ahmadu et al, 2020a;Fred-Ahmadu et al, 2020b;Lu et al, 2020;Na et al, 2020;Wilcox et al, 2020;Wong et al, 2020;Yu and Chan, 2020). Microplastics (MPs; 0.1 µm-5 mm) and nanoplastics (NPs; <0.1 µm) are ubiquitous and can accumulate in marine and freshwater ecosystems and exposed organisms, carrying chemical contaminants that are capable of posing considerable threats to human health, environment and aquatic life (de Souza Machado et al, 2018;Hartmann et al, 2019;Cole et al, 2020;Xu et al, 2020). Micro (nano) plastics (MNPs) are generally speculated to have increased environmental and health threats to marine organisms primarily due to their small size, predicted ubiquitousness, direct and indirect intake of plastic particles, bioavailability and enhanced concentrations of sorbed toxic chemicals (Setälä et al, 2018;Yu et al, 2018;Cole et al, 2020;Fred-Ahmadu et al, 2020a;Fred-Ahmadu et al, 2020b;Xu et al, 2020;Yu and Chan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Microplastics (MPs; 0.1 µm-5 mm) and nanoplastics (NPs; <0.1 µm) are ubiquitous and can accumulate in marine and freshwater ecosystems and exposed organisms, carrying chemical contaminants that are capable of posing considerable threats to human health, environment and aquatic life (de Souza Machado et al, 2018;Hartmann et al, 2019;Cole et al, 2020;Xu et al, 2020). Micro (nano) plastics (MNPs) are generally speculated to have increased environmental and health threats to marine organisms primarily due to their small size, predicted ubiquitousness, direct and indirect intake of plastic particles, bioavailability and enhanced concentrations of sorbed toxic chemicals (Setälä et al, 2018;Yu et al, 2018;Cole et al, 2020;Fred-Ahmadu et al, 2020a;Fred-Ahmadu et al, 2020b;Xu et al, 2020;Yu and Chan, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For D. magna , mortality [ 61 ], decreased reproduction [ 61 , 62 , 63 , 64 ] decreased growth and population growth rate [ 62 ] has been shown for virgin 1–6 µm MP spheres (polymeric composition not reported, PE and PS) from concentrations as low as 0.1 mg/L [ 62 ]. Similarly, adverse effects on Daphnia longevity, growth, reproduction [ 65 , 66 ] and physiological endpoints (heart and appendage beat rate) [ 44 ] have also been demonstrated upon PS nanosphere exposures. Physical properties of the MP are essential regarding inducing of adverse effects [ 46 ] and facilitated MP uptake by various routes (orally, anally) by D. magna (or other organisms) and moreso, inhibited egestion may be one of the most important triggers leading to adverse effects, especially over a longer exposure period.…”
Section: Discussionmentioning
confidence: 99%
“…Again, these studies have been conducted on virgin plastics with a few exceptions in studied MP from consumer products. Xu et al [ 44 ] showed exposure to post-consumer mixed plastic leachate containing differently sized MP did not affect survival of D. magna , but increased growth and reproduction that was attributed to hormesis and the potential role of plastic additives. Schür et al [ 45 ] showed irregular PS MP to affect D. magna life-history endpoints differently from natural kaolin particles.…”
Section: Introductionmentioning
confidence: 99%